1997
DOI: 10.1111/j.1540-8159.1997.tb05457.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Automatic Processing and Reliability of Stored Data in an Implanted Pacemaker: Initial Results in 59 Patients

Abstract: Stored data in implantable pacemakers have rarely been used as a diagnostic tool because of the complexity. Our group has developed software called AIDA, providing an automatic interpretation of data stored in memories of the Chorus (ELA medical) pacemaker. We compared the results of AIDA analysis to surface ECG Holter interpretation in 59 patients (age 75 +/- 9 years). In 33 cases, neither AIDA nor the Holter found any anomaly. Eleven patients demonstrated episodes of supraventricular tachycardia (SVT), confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…The ELA algorithm for identifying atrial arrhythmias detected atrial arrhythmias verified by ambulatory monitoring with 93% sensitivity and 94.2% specificity. 3,17 Our ambulatory monitoring sample, although small, provided almost identical sensitivity and specificity results to these prior studies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The ELA algorithm for identifying atrial arrhythmias detected atrial arrhythmias verified by ambulatory monitoring with 93% sensitivity and 94.2% specificity. 3,17 Our ambulatory monitoring sample, although small, provided almost identical sensitivity and specificity results to these prior studies.…”
Section: Discussionsupporting
confidence: 63%
“…The AIDA study compared stored pacemaker data to Holter monitors and to patients' clinical history of symptoms. 3,17 The AIDA investigators, like us, found a poor correlation between symptoms and the presence of AHRE detected by the pacemaker. Previous studies have shown that unlike paroxysmal SVT, which is usually symptomatic, paroxysmal atrial fibrillation is often entirely asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concept of a diagnostic pacemaker emerged from the need to document arrhythmias suspected to be responsible for unexplained syncope [11,14,15]. The new AIDA software, installed in the pacemaker programmer, provides an automatic interpretation of the data stored in the memory of Chorus pacemakers, and offers diagnostic assistance [12]. The separate activity of both cardiac chambers can be observed, premature complexes are counted, and atrial arrhythmias leading to changes in the pacemaker's operating mode are represented with clearly visible onset and offset.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors call them as “intelligent pacemakers,” because of their more precise information storage, such as electrocardiographic telemetry and event markers and counters. This set of resources is supposed to allow a constant diagnostic monitoring and, consequently, an improvement of the therapeutic management of the patients …”
Section: Introductionmentioning
confidence: 99%